Therapeutic effect of biosynthesized silver nanoparticles on hypothyroidism induced in albino rats - Ebrahim Saied; Ahmed S. Hussein; Abdulaziz A. Al-Askar; Nadeem I. Elhussieny; Amr H. Hashem (Electronic Journal of Biotechnology, 2023)
Background: In this study, silver nanoparticles (AgNPs) were biosynthesized using Rhizopus oryzae. The therapeutic effect of AgNP treatment protocols for hypothyroidism induced in male albino rats via biochemical as well as hematological parameters, thyroid profile, and androgen male sex hormone (testosterone) was evaluated. Results: FTIR, XRD, TEM, DLS, SEM, and EDX were used to comprehensively characterize the biosynthesized AgNPs. The AgNPs have a 17–35 nm diameter, according to the results of their characterization. The average size detected by XRD was 37.96 nm, while the average size of the biosynthesized AgNPs was 78 nm determined by DLS analysis. Furthermore, ALT, AST activity, urea, creatinine, and TSH levels revealed a significant increase in the untreated hypothyroidism group according to potassium dichromate-induced hypothyroidism compared to the normal control group. The untreated hypothyroidism group's FT3, FT4, and albumin levels, however, significantly decreased when compared to the normal control group. In contrast, when compared to the hypothyroidism-untreated group, the mean values of FT3, FT4, and TSH were all significantly higher and TSH was significantly lower in the hypothyroidism AgNPS-treated group. Furthermore, T. testosterone and F. testosterone levels revealed a significant decrease in untreated hypothyroidism group when compared to the normal control group. Contrarily, F. testosterone levels in the hypothyroidism-treated group were much higher than those in the hypothyroidism-untreated group. Conclusions: AgNPs were successfully biosynthesized which exhibited therapeutic potential to increase thyroid hormone levels and avoid the biochemical side effects of thyroid hormone deficiency in the animal model of hypothyroidism.How to cite: Saied E, Hussein AS, Al-Askar AA, et al. Therapeutic effect of biosynthesized silver nanoparticles on hypothyroidism induced in albino rats. Electron J Biotechnol 2023;65. https://doi.org/10.1016/j.ejbt.2023.06.001.